Emergency department evaluation of blunt abdominal trauma in children: a systematic review and meta-analysis of patterns and outcomes - Alsubhi, Huda; Suliman, Osman; Alsubhi, Amal; Altom, Sara (International Journal Of Community Medicine And Public Health, 2025)
Blunt abdominal trauma is a leading cause of morbidity and mortality in children. Accurate and timely evaluation in the emergency department is critical for optimizing outcomes and minimizing unnecessary imaging or interventions. Objective of the study was to systematically review current evidence on evaluation patterns, diagnostic modalities, and clinical outcomes in pediatric patients presenting with blunt abdominal trauma to emergency departments. A systematic literature search was conducted in PubMed, Scopus, and Web of Science from January 2010 to June 2025. Studies reporting diagnostic approaches, imaging patterns, injury severity, management, and patient outcomes in children under 18 years were included. Data were extracted and synthesized qualitatively and quantitatively where appropriate. Twenty-two studies comprising 18,950 pediatric patients were analyzed. Physical examination combined with focused assessment with sonography for trauma (FAST) increased diagnostic accuracy and reduced computed tomography (CT) utilization. Non-operative management remained the mainstay for most solid organ injuries, with excellent survival rates exceeding 95 percent. Delayed diagnosis was associated with higher complication rates and prolonged hospital stays. Systematic evaluation protocols, including selective imaging and observation strategies, improve diagnostic precision and outcomes in pediatric blunt abdominal trauma. Future research should focus on refining risk stratification tools to further reduce radiation exposure without compromising safety.